De-escalating and escalating treatment beyond endocrine therapy in patients with luminal breast cancer. (August 2017) - McCartney, Amelia; Vignoli, Alessia; Hart, Christopher; Tenori, Leonardo; Luchinat, Claudio; Biganzoli, Laura; Di Leo, Angelo
Abstract: Luminal breast cancers demonstrate significant molecular and clinical heterogeneity, despite the commonality of shared expression of the estrogen receptor (ER). To date, no clinical trial has prospectively investigated the optimal chemotherapy regime according to luminal type, highlighting a paucity of data furthermore required to guide treatment decisions. Current methods of predicting advantage from adjuvant chemotherapy lack refinement and can over-estimate the risk of relapse, inevitably leading to a proportion of patients being unnecessarily exposed to chemotherapy. This paper will explore the evidence behind modalities which may add further value to existing known clinicopathological and molecular profiling techniques in predicting clinical benefit from chemotherapy. Adjuvant chemotherapy regime choice in the context of early luminal breast cancer types will be discussed, and areas for further research and debate identified.